Cathelicidin Peptides Inhibit Multiply Antibiotic-Resistant Pathogens from Patients with Cystic Fibrosis - Saiman, Lisa (American Society for Microbiology, 2001)
Endogenous peptide antibiotics are under investigation as inhaled therapeutic agents for cystic fibrosis (CF) lung disease. The bactericidal activities of five cathelicidin peptides (LL37 [human], CAP18 [rabbit], mCRAMP [mouse], rCRAMP [rat], and SMAP29 [sheep]), three novel alpha-helical peptides derived from SMAP29 and termed ovispirins (OV-1, OV-2, and OV-3), and two derivatives of CAP18 were tested by broth microdilution assays. Their MICs were determined for multiply antibiotic-resistant Pseudomonas aeruginosa (n = 24), Burkholderia cepacia (n = 5), Achromobacter xylosoxidans (n = 5), and Stenotrophomonas maltophilia (n = 5) strains isolated from CF patients. SMAP29 was most active and inhibited mucoid and nonmucoid P. aeruginosa strains (MIC, 0.06 to 8 μg/ml). OV-1, OV-2, and OV-3 were nearly as active (MIC, 0.03 to 16 μg/ml), but CAP18 (MIC, 1.0 to 32 μg/ml), CAP18-18 (MIC, 1.0 to >32 μg/ml), and CAP18-22 (MIC, 0.5 to 32 μg/ml) had variable activities. LL37, mCRAMP, and rCRAMP were least active against the clinical isolates studied (MIC, 1.0 to >32 μg/ml). Peptides had modest activities against S. maltophilia and A. xylosoxidans (MIC range, 1.0 to > 32 μg/ml), but none inhibited B. cepacia. However, CF sputum inhibited the activity of SMAP29 substantially. The effects of peptides on bacterial cell membranes and eukaryotic cells were examined by scanning electron microscopy and by measuring transepithelial cell resistance, respectively. SMAP29 caused the appearance of bacterial membrane blebs within 1 min, killed P. aeruginosa within 1 h, and caused a dose-dependent, reversible decrease in transepithelial resistance within 5 h. The tested cathelicidin-derived peptides represent a novel class of antimicrobial agents and warrant further development as prophylactic or therapeutic agents for CF lung disease.